Diversification of Aquaculture in the Sub-Saharan Region—The Obscure Snakehead - Sven Wuertz; Amien Isaac Amoutchi; Johnny Ogunji (Fishes)
The sub-Saharan region shows fast growth in aquaculture, but current production is dominated by two species, the African catfish and tilapia. In order to support the expansion of the industry and ensure food resilience of the sector, diversification is desirable. Indeed, several candidates have been identified, among them the African snakehead Parachanna obscura. In contrast to the fast expansion of Asian snakehead farming, African aquaculture does not anticipate this trend. Still, looking at Asia, recent scientific literature provides impulses and solutions for the most pressing problems such as dry feed, cannibalism of juvenile stages and reproduction. In this review, we illustrate future research needs, integrating the recent progress in snakehead farming. Based on the recent progress in commercial diets in Clarias and protocols established for the reproduction of Channa species, an expansion of African snakehead farming seems feasible in the near future.